Assessment of the quality of mobile applications for smoking cessation and its potential for the modification of psychosocial and behavioral risk factors for cardiovascular disease - K. A. Zamyatin; D. I. Nozdrachev; D. G. Kakadzhikova; U. V. Golovanova; G. A. Varaksin (Российский кардиологический журнал, 2022)
Aim. To analyze the functionality and characteristics of quit smoking applications available to Russian-speaking users using validated scales for its evaluation.Material and methods. Applications were searched in the App Store and Google Play, and a specialized MARS scale was used to evaluate applications. A total of 598 applications were found, of which 54 applications met the inclusion criteria and were included in the study.Results. It was found that 54% of applications use short- and medium-term goals as methods and techniques to increase the likelihood of quitting tobacco, while 31% of applications use various educational materials in order to form a negative attitude towards smoking. In addition, 22% of applications use cognitive and behavioral techniques of cognitive behavioral therapy. A negative moderate correlation was established between the application user rating and MARS score (r=-0,32).Conclusion. The Russian-language anti-smoking mobile applications included in this study demonstrated satisfactory quality on average. A significant number of applications use proven effective cognitive behavioral therapy techniques. At the same time, mobile applications in healthcare has shortcomings, especially in terms of compliance with guidelines, and needs to be further improved.